Hubungan Low Self-Acceptance Dengan Tingkat Self-Efficacy Pada Narapidana Terhadap Kehidupan Sosial Bermasyarakat - Renata Dian Firmadani (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study aims to determine the relationship between low self-acceptance and the level of self-efficacy in prisoners, as well as its implications on social life after prisoners are released from punishment. The systematic review method is used with the SPIDER approach to formulate research questions and select relevant articles. The search was conducted through the Publish or Perish, Google Scholar, and Scopus databases with keywords related to self-acceptance, self-efficacy, and inmates. Of the 100 articles identified, 13 studies met the inclusion criteria. The results of the review showed that low self-acceptance was consistently negatively associated with self-efficacy in prisoners, which had an impact on low self-confidence to face social challenges, reintegration, and overcome societal stigma. Psychological factors such as guilt, anxiety, depression, and insecurity can exacerbate low self-acceptance, especially in female inmates. In addition, social support from family, the environment, and psychological interventions have been shown to play an important role in improving self-acceptance and self-efficacy. Interventions such as expressive art therapy, psychoeducation, counseling, skills training, and religious activities have shown effectiveness in improving psychological well-being. These findings underscore the importance of systematic efforts to improve self-acceptance and self-efficacy to support the successful social reintegration of prisoners.